Prediction of reservoir sedimentation using Soil Water Assessment Tool (SWAT) towards development of sustainable catchment management - Abdul Razad A.Z.; Sidek L.M.; Jung K.; Rahman N.F.; Shamsuddin S.H. (Institute of Physics Publishing, 2023)
Sedimentation is considered as one of the major deterioration of a lake or reservoir, resulted from the sediment yield process in the catchment. To control reservoir sedimentation, the most effective method is to control sediment production at sources. This studyis initiated to determine reservoir sedimentation using Soil and Water Assessment Tool (SWAT). Cameron Highlands is an active agricultural area is chosen as study area, where meteorological data from 1997 to 2012 were used to simulate stream flow and sediment load at main rivers feeding into Ringlet Reservoir. Sensitivity analyses were conducted to determine the most sensitive parameters towards flow and sediment load simulation. Calibration and validation were performed from 2001 to 2006 and 2010 to 2012 respectively. Model performance ranges from satisfactory to good, as indicated by R2.0.5, NSE > 0.5, PBIAS <+10% and RSR<0.7. Results are in the form of spatial distribution of flow, sediment load and sediment yield, which are useful to determine problematic sub-catchment to prompt for immediate sediment control measures. Published under licence by IOP Publishing Ltd.